HEPATIC ADENOMATOSIS IN A 32-YEAR-OLD MALE WITH NO RISK FACTORS FOR HEPATIC ADENOMA - Malik, Talia Farrukh; Akram, Salma (Journal of Ayub Medical College Abbottabad, 2022)
Hepatic Adenomatosis most commonly arises in the background of hepatic adenoma in young women and less commonly in men with underlying risk factors. Rarely, it can arise in young men with none of the associated risk factors and thus can go undetected for a prolonged period resulting in delayed intervention and avoidable complications. We present a rare case of a 32-year-old asymptomatic male that presented for routine evaluation and was subsequently diagnosed with Hepatic Adenomatosis.